Neural Correlates of Enhanced Memory for Meaningful Associations with Age - Amer, Tarek (Cereb Cortex, 2019)
Evidence suggests that age differences in associative memory are attenuated for associations that are consistent with prior knowledge. Such knowledge structures have traditionally been associated with the default network (DN), which also shows reduced modulation with age. In the present study, we investigated whether DN activity and connectivity patterns could account for this age-related effect. Younger and older adults underwent functional magnetic resonance imaging as they learned realistic and unrealistic prices of common grocery items. Both groups showed greater activity in the DN during the encoding of realistic, relative to unrealistic, prices. Moreover, DN activity at encoding and retrieval and its connectivity with an attention control network at encoding were associated with enhanced memory for realistic prices. Finally, older adults showed overactivation of control regions during retrieval of realistic prices relative to younger adults. Our findings suggest that DN activity and connectivity patterns (traditionally viewed as indicators of cognitive failure with age), and additional recruitment of control regions, might underlie older adults’ enhanced memory for meaningful associations.